1996
DOI: 10.1021/cm9505299
|View full text |Cite
|
Sign up to set email alerts
|

Aluminosilicate Nanocomposite Materials. Poly(ethylene glycol)−Kaolinite Intercalates

Abstract: This paper reports the first example of the direct intercalation of an organic polymer into the interlamellar spaces of kaolinite. Poly(ethylene glycols) (PEG 3400 and PEG 1000) were intercalated into kaolinite by displacing dimethyl sulfoxide (DMSO) from the DMSO−kaolinite intercalate (Kao−DMSO). This was done directly from the polymer melt at temperatures between 150 and 200 °C. XRD showed that the intercalated oxyethylene units were arranged in flattened monolayer arrangements, such that the interlayer expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
121
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(131 citation statements)
references
References 71 publications
8
121
0
2
Order By: Relevance
“…The XRD study of these materials confirmed that the intercalated oxyethylene units are arranged in flattened monolayer arrangements with 4 Å interlayer expansions [5]. It is supported by trans conformation to at least a portion of (O-CH 2 -CH 2 -O) groups of the PEG chain [48]. Furthermore, the main driving force for the intercalation reaction results from orientation of the polymer chains such that they form hydrogen bond with the hydroxylated aluminate surfaces of the clay.…”
Section: Ac Conductivity Spectramentioning
confidence: 77%
See 2 more Smart Citations
“…The XRD study of these materials confirmed that the intercalated oxyethylene units are arranged in flattened monolayer arrangements with 4 Å interlayer expansions [5]. It is supported by trans conformation to at least a portion of (O-CH 2 -CH 2 -O) groups of the PEG chain [48]. Furthermore, the main driving force for the intercalation reaction results from orientation of the polymer chains such that they form hydrogen bond with the hydroxylated aluminate surfaces of the clay.…”
Section: Ac Conductivity Spectramentioning
confidence: 77%
“…The structural properties and dynamical behaviour of these phases governs the electrical conductivity of the organic-inorganic nanocomposite [45]. The PEO-clay and PEG-clay nanocomposites are extensively attempted to make potential electrolyte material for rechargeable batteries [8,9,[46][47][48][49][50][51][52]. Different spectroscopy investigation on poly(ethylene oxide) PEO-clay nanocomposites [46] confirmed that the intercalated PEO molecules between silicate galleries impede the polymer crystallization, which results in higher electrolyte conductivity compared to the system without clay.…”
Section: Ac Conductivity Spectramentioning
confidence: 97%
See 1 more Smart Citation
“…A intercalação de algumas moléculas particulares somente é possível através do deslocamento de outras moléculas previamente intercaladas [10][11][12][13][14][15][16] . Recentemente, a intercalação de polímeros também foi reportada 12,[17][18][19][20] utilizando-se a metodologia de intercalação do precursor seguida de polimerização térmica 12,20 , intercalação do polímero fundido com caulinita previamente expandida 17,18 , ou deslocamento de moléculas de água previamente intercaladas 19,20 . Um dos derivados obtidos durante o processo de lavagem da caulinita previamente intercalada é a caulinita hidratada [21][22][23] .…”
Section: Introductionunclassified
“…According to these papers [4]- [6], the clay mineral includes two layers of silicon-oxygen tetrahedral, facing each other by their peaks, that on both sides covered by the layer of Aluminohydroxyl octahedral, which in general appears to be a three-layer packet (2: 1).…”
Section: Resultsmentioning
confidence: 99%